Late Quaternary environments on the far southwestern edge of Beringia. (1st January 2019) - Lozhkin, A.V.; Anderson, P.M.; Glushkova, O. Yu; Vazhenina, L.N.
Abstract: Palynological and plant macrofossil data and remains of Mammuthus primigenius from the Tanon quarry (59° 40′ N, 151° 12′ E) provide much needed information about environments in southwestern Beringia during the Middle Holocene and marine isotope stages (MIS) 2 and 3. During the Middle Holocene, Larix-Betula forest characterized the Tanon region and differed from the Larix forests of interior Western Beringia. Betula platyphylla, which today is more common in moderate regions of the Far East, was an important component of the coastal forest near the quarry and possibly was more extensive in the coastal lowland. Ecological and quantitative models suggest that the coastal region experienced longer growing seasons and warmer summer temperatures, which could support the expansion of tree Betula . The MIS 2 palynological assemblage from Tanon indicates a prevalence of mesic and xeric herb-dominated tundra. However, the macrofossil data consist largely of taxa found in forest or forest-tundra with only a minor contribution by steppe species. The Tanon results agree with the larger paleovegetation database from Beringia, which suggests that steppe was not widespread during the Late Pleistocene but rather the landscape was characterized by a mosaic of tundra types. The Tanon site provides the first information about MIS 3 coastal vegetation, indicating the presence of Larix-Betula forest within valleys and shrub tundra at higher elevations. The discovery of Mammuthus primigenius in the quarry marks the southernmost population of Late Pleistocene mammoths in Western Beringia. Highlights: Late Pleistocene vegetation in southwest Beringia was a tundra-forest mosaic. Tanon site documents the southernmost population of mammoth in Western Beringia. Mammoth-steppe should no longer be used when describing Beringian environments. Mid-Holocene of southwest Beringia is characterized by a unique Larix-Betula forest. Priokhot'ye had warmer summers and longer growing seasons during the Mid-Holocene.